Tuning secondary structure and self-assembly of amphiphilic peptides - Löwik, Dennis W P M; Garcia-Hartjes, Jaime; Meijer, Joris T; van Hest, Jan C M (Langmuir, 2005)
Self-assembly is one of nature's mechanisms by which higher order structures are obtained. Two of the main driving forces for self-assembly, hydrophobic interactions and hydrogen bonding, are both present within amphiphilic peptides. Here, it is demonstrated how the intricately interconnected folding and assembly behavior of an N-terminally acylated peptide, with the sequence GANPNAAG, has been tuned by varying its hydrophobic tail and thermal history. The change in interplay between hydrophobic forces and peptide folding allowed the occurrence of different types of aggregation, from soluble peptides with a random coil conformation to aggregated peptides arranged in a beta-sheet assembly, which form helically twisted bilayer ribbons.